Proceedings of the 53rd Annual Meeting of the Association for Computational Linguistics and the 7th International Joint Confere 2015
DOI: 10.3115/v1/p15-1157
|View full text |Cite
|
Sign up to set email alerts
|

A Frame of Mind: Using Statistical Models for Detection of Framing and Agenda Setting Campaigns

Abstract: Framing is a sophisticated form of discourse in which the speaker tries to induce a cognitive bias through consistent linkage between a topic and a specific context (frame). We build on political science and communication theory and use probabilistic topic models combined with time series regression analysis (autoregressive distributed-lag models) to gain insights about the language dynamics in the political processes. Processing four years of public statements issued by members of the U.S. Congress, our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 34 publications
0
90
0
Order By: Relevance
“…Several previous works have explored framing in public statements, congressional speeches, and news articles (Fulgoni et al, 2016;Tsur et al, 2015;Card 1 http://psl.cs.umd.edu Baumer et al, 2015). Our approach builds upon the previous work on frame analysis of Boydstun et al (2014), by adapting and applying their annotation guidelines for Twitter.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous works have explored framing in public statements, congressional speeches, and news articles (Fulgoni et al, 2016;Tsur et al, 2015;Card 1 http://psl.cs.umd.edu Baumer et al, 2015). Our approach builds upon the previous work on frame analysis of Boydstun et al (2014), by adapting and applying their annotation guidelines for Twitter.…”
Section: Related Workmentioning
confidence: 99%
“…While the first frame supports increasing minimum wage because it improves workers' lives, the second frame, by conversely emphasizing the costs involved, opposes the increase. Using framing to analyze political discourse has gathered significant interest over the last few years (Tsur et al, 2015;Card et al, 2015;Baumer et al, 2015) as a way to automatically analyze political discourse in congressional speeches and political news articles. Different from previous works which focus on these longer texts or single issues, our dataset includes tweets authored by all members of the U.S. Congress from both parties, dealing with several policy issues (e.g., immigration, ACA, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous works have explored framing in public statements, congressional speeches, and news articles (Fulgoni et al, 2016;Tsur et al, 2015;Card et al, 2015;Baumer et al, 2015). Framing is further related to works which analyze biased language (Recasens et al, 2013;Choi et al, 2012;Greene and Resnik, 2009) and subjectivity (Wiebe et al, 2004).…”
Section: Related Workmentioning
confidence: 99%
“…Framing contextualizes the discussion by emphasizing specific aspects of the issue, which creates an association between the issue and a specific frame of reference. Research on issue framing in political discourse is rooted in social science research (Entman, 1993;Chong and Druckman, 2007) and recently has attracted growing interest in the natural language processing community (Tsur et al, 2015;Card et al, 2015;Baumer et al, 2015) as a way to automatically analyze political discourse in congressional speeches and political news articles. Contrary to these sources, Twitter requires politicians to compress their ideas and reactions into 140 character long tweets.…”
Section: Introductionmentioning
confidence: 99%
“…Boydstun et al further suggested that hierarchical topic models can be used for identifying frames. Tsur et al (2015) also considered various contexts of a specific topic as frames and tried to infer these frames using topic models and time series. In a related study, Nguyen et al (2015) used hierarchical topic models to model issues and the associated "frames".…”
Section: Related Workmentioning
confidence: 99%